MENGGERAKKAN BUDAYA LITERASI: STRATEGI DAN TANTANGAN DALAM MENINGKATKAN MINAT BACA DI SEKOLAH DASAR - Diana, Anisa; Wafiqni, Nafia; Herianingtyas, Nur Luthfi Rizqa (Elementar : Jurnal Pendidikan Dasar, 2024)
This research aims to describe the implementation and constraints of the literacy movement carried out by MI Al-Hidayah Cirendeu. This type of research is descriptive with a qualitative approach. The techniques used in data collection are: observation, interviews and documentation. Data analysis techniques include: data reduction, data presentation, and conclusion drawing. The selection of informants used purposive sampling. The results revealed that the implementation of the school literacy movement at MI Al-Hidayah Cirendeu has familiarized its school community with reading for ±15 minutes in each class. Literacy at MI Al-Hidayah Cirendeu has carried out up to the learning stage by organizing library visits, providing reading corners in each classroom, writing, telling, and procuring literacy-rich banner posters. The main supporting factor in the school literacy movement at MI Al-Hidayah Cirendeu is the involvement of parents in book procurement by presenting reading books that are in accordance with children's age development. While the obstacles found, namely low interest in reading due to lack of student focus, limited reading time can cut class hours, facilities and infrastructure for literacy activities are still limited, and library management is less than optimal.